2022
DOI: 10.1302/2633-1462.37.bjo-2022-0044.r1
|View full text |Cite
|
Sign up to set email alerts
|

Undergraduate education of trauma and orthopaedic surgery in the UK

Abstract: Aims Evidence exists of a consistent decline in the value and time that medical schools place upon their undergraduate orthopaedic placements. This limited exposure to trauma and orthopaedics (T&O) during medical school will be the only experience in the speciality for the majority of doctors. This review aims to provide an overview of undergraduate orthopaedic training in the UK. Methods This review summarizes the relevant literature from the last 20 years in the UK. Articles were selected from database s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…The included studies highlighted the variability in screening practice throughout the UK, with a variety of reported clinical and ultrasound screening methods. All papers reported on selective screening, except for Westacott et al [15], whose study compared universal with selective screening.…”
Section: Resultsmentioning
confidence: 99%
“…The included studies highlighted the variability in screening practice throughout the UK, with a variety of reported clinical and ultrasound screening methods. All papers reported on selective screening, except for Westacott et al [15], whose study compared universal with selective screening.…”
Section: Resultsmentioning
confidence: 99%
“…However, these day-long one-off, occasionally annual events 12–16 were only available to a small number of students and rely on the willingness of proactive students to give up their time outside of the core curriculum. Furthermore, there were no studies that demonstrated a sustained improvement in surgical skills at follow-up, which has been shown to be an important marker of educational efficacy 32 , 33 . Clearly, this is not an appropriate way to address the deficit as it only benefits a small number of students and has not demonstrated long-term improvement.…”
Section: Discussionmentioning
confidence: 99%
“…Several schools have attempted to bridge this gap using CBLs, in post-graduate and undergraduate training, and have found them effective. This is true for other serious but less common conditions where a fair amount of competency is expected (Burke et al, 2023;Chen et al, 2023;Poacher et al, 2022).…”
Section: Cbl As a Tool To Bridge Gaps In Experiencementioning
confidence: 98%